(untitled) (Research, Society and Development, 2020)
Technological advancements are increasingly transforming personal and social relationships. Despite the efforts that have been made to promote the use of technologies in education, there are still hardships when it comes to incorporating them into teaching practice. This study aims to identify some digital educational platforms targeted at primary and secondary education in Brazil. The platforms were analyzed as to the relevance of their contents to primary and secondary education, as well as to the dynamism of those environments regarding virtual learning objects and content creation features made available to students and/or teachers in such digital environments. The study outlines topics such as 21st century education and society, and digital information and communication technologies, in addition to a discussion section and some final remarks. As a result, it shows evidence of the need for new platforms that would not only provide content, but also allow authorship and protagonism among primary and secondary education students as regards the creation of content and virtual learning objects.